2020
DOI: 10.1155/2020/8858415
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic System in Stress: Implications of GABAergic Neuron Subpopulations and the Gut-Vagus-Brain Pathway

Abstract: Stress can cause a variety of central nervous system disorders, which are critically mediated by the γ-aminobutyric acid (GABA) system in various brain structures. GABAergic neurons have different subsets, some of which coexpress certain neuropeptides that can be found in the digestive system. Accumulating evidence demonstrates that the gut-brain axis, which is primarily regulated by the vagus nerve, is involved in stress, suggesting a communication between the “gut-vagus-brain” pathway and the GABAergic neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…These altered behavioral responses in SR-KO mice could be associated with the reduced inhibitory tone induced by d -serine removal. Indeed, modulation of GABA activity is known to alter several behaviors such as locomotor activity, anxiety-related behaviors, and memory [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These altered behavioral responses in SR-KO mice could be associated with the reduced inhibitory tone induced by d -serine removal. Indeed, modulation of GABA activity is known to alter several behaviors such as locomotor activity, anxiety-related behaviors, and memory [ 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, dietary GABA enhances the postprandial activation of vagal afferents, thereby potentiating postprandial satiation. Recent growing evidence has indicated that gut-brain signal-related vagal afferents and gut microbiota influence emotional behaviors [52][53][54][55]; thus, dietary GABA might act on the gutbrain axis to treat stress-related disorders. By clarifying the detailed mechanism of vagal afferent activation by dietary GABA, the control of vagal nerve activity by dietary GABA might become a useful tool for improving brain functions including feeding, metabolism, and other mental functions.…”
Section: Discussionmentioning
confidence: 99%
“…Gabra6 has been genetically linked to human alcohol dependence [68][69][70] and variations in human stress response [71,72]. Indeed, the GABAergic system is widely known as a critical regulator of stress responses and is a common drug target for the treatment of stress-related psychiatric conditions (depression, anxiety) [73]. Gabra6 and Gabrd were also both upregulated in the brains of alcohol-drinking P rats [74].…”
Section: Discussionmentioning
confidence: 99%